ANALISIS KESUKSESAN IMPLEMENTASI MODUL APPROWEB MENU CRM: STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA WATAMPONE - Muh. Ihsan A.R.; Azwar Azwar (JURNAL INFO ARTHA, 2024)
This research aims to evaluate the success of the Approweb module, especially the CRM menu/aspect and Trigger Data & Tester Data, based on the user's perspective using the Information Systems Success Model approach by DeLone & McLean (1992). This research uses a quantitative approach through component or variant-based Structural Equation Modeling (SEM) modeling techniques with Partial Least Square (PLS). The results of the research show that the implementation of the Approweb system/module (CRM and Trigger Data & Tester Data) at KPP Pratama Watampone has been empirically proven not to be completely running well and successfully based on the DeLone and McLean model indicators or approaches. Of the seven hypotheses proposed, not all of them are proven and acceptable. Therefore, it is hoped that DJP can continue to improve the quality of the system or module, considering that there are still several weaknesses in its use in the field.